Find f ( 3 1 0 ) , if f ( x + 3 ) = f ( x ) − x 2 + x − 5 for all real numbers x , and f ( 1 ) = 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f ( 1 ) = 3 f ( 1 + 3 ) = f ( 4 ) = f ( 1 ) − 1 2 + 1 − 5 f ( 4 + 3 ) = f ( 7 ) = f ( 4 ) − 4 2 + 4 − 5 = f ( 1 ) − 1 2 + 1 − 5 − 4 2 + 4 − 5 f ( 7 + 3 ) = f ( 1 0 ) = f ( 7 ) − 7 2 + 7 − 5 = f ( 1 ) − 1 2 + 1 − 5 − 4 2 + 4 − 5 − 7 2 + 7 − 5 ⋯ f ( 3 0 7 + 3 ) = f ( 3 1 0 ) = f ( 3 0 7 ) − 3 0 7 2 + 3 0 7 − 5 = f ( 1 ) − 1 2 + 1 − 5 − 4 2 + 4 − 5 − 7 2 + 7 − 5 ⋯ − 3 0 4 2 + 3 0 4 − 5 − 3 0 7 2 + 3 0 7 − 5 f ( 1 ) + n = 0 ∑ 1 0 2 ( − ( 3 n + 1 ) 2 + ( 3 n + 1 ) − 5 ) = − 3 2 4 6 8 6 6
I'm lazy. So, I got a computer to calculate it for me...
var y = 3;
var x = 1;
for (var i = 1; i <= 310; i += 3) {
console.log(x, y)
y = y - (x*x) + x - 5;
x += 3;
}
Problem Loading...
Note Loading...
Set Loading...
The condition f ( x + 3 ) = f ( x ) − x 2 + x − 5 gives a simple set of simultaneous equations for the coefficients of f ( x ) . Since the degree of f ( x + 3 ) − f ( x ) must be one less than the degree of f ( x ) , it is clear that f ( x ) must be cubic and solving the simultaneous equations tells us that f ( x ) = − 9 1 x 3 + 3 2 x 2 − 3 8 x + d for some constant d . Since f ( 1 ) = 3 we deduce that d = 9 4 6 . Hence f ( 3 1 0 ) = − 3 2 4 6 8 6 6 .